2022
DOI: 10.1001/jamanetworkopen.2022.36609
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Time Interval from COVID-19 Vaccination to In Vitro Fertilization and Pregnancy Rate After Fresh Embryo Transfer

Abstract: ImportanceThere is a lack of information regarding the need to postpone conception after COVID-19 vaccination.ObjectiveTo investigate the time interval between the first dose of inactivated COVID-19 vaccine and in vitro fertilization (IVF) treatment as well as the rate of pregnancy after a fresh embryo transfer.Design, Setting, and ParticipantsThis cohort study was conducted at a single public IVF center in China. Female patients aged 20 to 47 years and undergoing IVF treatment were consecutively registered fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 19 publications
2
35
0
Order By: Relevance
“…Twelve studies analyzed clinical pregnancy rate, no difference was observed in all the studies (30-34, [36][37][38][39][40][41][42] and also in our study.…”
Section: Clinical Pregnancy Ratementioning
confidence: 45%
“…Twelve studies analyzed clinical pregnancy rate, no difference was observed in all the studies (30-34, [36][37][38][39][40][41][42] and also in our study.…”
Section: Clinical Pregnancy Ratementioning
confidence: 45%
“…Author affiliations and article information are listed at the end of this article. Shi et al 4 addressed an important question with a large group of patients, but there are a couple of important limitations to discuss. Although the overall sample size of the study is large, the subgroups who received vaccination 30 days or less (n = 35) and 30 to 60 days (n = 58) before undergoing IVF were relatively small.…”
Section: + Related Articlementioning
confidence: 99%
“…Of importance, the vaccines received by participants in the study by Shi et al 4 were all inactivated-virus vaccines that were available in China where the study was performed. These results should, therefore, be generalized with extreme caution, as they may not be applicable or reproducible in the US, where most of the vaccines administered have been mRNA based (eg, BNT162b2 [Pfizer-BioNTech] and mRNA-1273 [Moderna]).…”
mentioning
confidence: 99%
See 2 more Smart Citations